Estética marxista e educação: formação para a emancipação humana - Debiazi , Marcia da Silva Magalhães (2013)
This present paper analyzes the idea of Marxist aesthetic in its own theoretical field and suggests the importance as an education tool, once it thinks in an omnilateral education with horizon in human emancipation. For this purpose, this thesis discusses the concept of aesthetics in Marx’s thought, mainly in his Economic and Philosophic Manuscripts. It was argued that this idea is better understood if located in the set of its thought. Its political and social philosophy says that the man just recognizes himself as a social being within the process of creation (work), when practices his subjectivities. However, with the capitalist mode of production this objectification becomes fragmented and strange to man. It is in this world of estrangement, of loss of itself, that the humanizing character of aesthetic education is placed, seen as a possibility for man to externalize his thought and so reflect critically about the world. It is understood, though, that there is no aesthetic object without an aesthetic subject. Therefore, there cannot be just one moment of artwork that can be designed independently from men, from human subjectivity, once there is no artistic production without men even if it is possible to objectify itself. Consequently, the appreciation of the aesthetic ideas of Marx cannot be separated from the human and artistic practice that it supports. The Marxist aesthetics seeks another dimension to artistic activity, since human senses are not just an expression of the spirit, as Hegel assumed, to become a mean of affirming the man. Our effort is to understand what is the Marxist aesthetics, what is its connection with work, since Marx does not reduce it only to sensory, but for him, art is inherent to the social being, or rather, the art is the human objectification. Marx understands art as a way of human objectification, the same as work, which is the primary and essential form of human contact with the world, in which daily origins and thoughts are found. Therefore, the artist, is also seen as a social being determined by historical circumstances in constant changing process, so the art is as well a way of human objectification just like work. According to Marx, alienation, objectification and externalization are ontological conditions of man. But the estrangement is a consequence of the existence of private property. For this reason, education assumes the Marxist aesthetics as subversive element of capitalism, a significant role in the creative process and critical thinking. Art is a social phenomenon. So, based on our theoretical reference, the aim of this investigation is, in some traits, to highlight the revolutionary potential of aesthetic education, based on Marxist ideas, to understand that it is an important creative, imaginary, critic, sensitive and perceptive field of the existent reality, and that it is often not seen outside the ideas of the ruling classes.